AHR Activation Is Protective against Colitis Driven by T Cells in Humanized Mice - Goettel, Jeremy A.; Gandhi, Roopali; Kenison, Jessica E.; Yeste, Ada; Murugaiyan, Gopal; Sambanthamoorthy, Sharmila; Griffith, Alexandra E.; Patel, Bonny; Shouval, Dror S.; Weiner, Howard L.; Snapper, Scott B.; Quintana, Francisco J. (Cell reports (Cambridge), 2016)
Existing therapies for inflammatory bowel disease that are based on broad suppression of inflammation result in variable clinical benefit and unwanted side effects. A potential therapeutic approach for promoting immune tolerance is the in vivo induction of regulatory T cells (Tregs). Here we report that activation of the aryl hydrocarbon receptor using the non-toxic agonist 2-(1′H-indole-3′-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE) induces human Tregs in vitro that suppress effector T cells through a mechanism mediated by CD39 and Granzyme B. We then developed a humanized murine system whereby human CD4+ T cells drive colitis upon exposure to 2,4,6-trinitrobenzenesulfonic acid and assessed ITE as a potential therapeutic. ITE administration ameliorated colitis in humanized mice with increased CD39, Granzyme B, and IL10-secreting human Tregs. These results develop an experimental model to investigate human CD4+ T responses in vivo and identify the non-toxic AHR agonist ITE as a potential therapy for promoting immune tolerance in the intestine. [Display omitted] •Non-toxic AHR agonist ITE induces human regulatory T cells in vitro•ITE-mediated in vitro suppression is dependent on CD39 and Granzyme B•Human CD4 T cells drive TNBS-induced colitis in humanized mice•ITE protects against TNBS-induced colitis in humanized mice Therapeutic approaches aimed at expanding regulatory T cells in the gut to promote immune tolerance in patients with inflammatory bowel disease (IBD) are of clinical significance. Goettel et al. establish a humanized murine model of IBD driven by human T cells and find that activation of AHR by the non-toxic agonist ITE can prevent experimental colitis.